Allowing Imprisoned Fathers to Parent: Maximising the Potential Benefits of Prison based Parenting Programmes. Issue 2 (3rd April 2018) - Hayes, David; Butler, Michelle; Devaney, John; Percy, Andrew
ABSTRACT: During imprisonment, fathers are separated from their families and contact is limited. When delivering a prison based parenting programme, providing an opportunity to rehearse newly acquired parenting skills can be key for mastering the performance of these skills and using these skills to improve father-child relationships. This paper takes an in-depth look at how one parenting programme in Northern Ireland sought to overcome this challenge by providing additional opportunities to parent via increased telephone contact and special family friendly visits. Using a combination of in-depth interviews and observations, how fathers and their families responded to this increased contact is explored, as well as the extent to which this increased contact facilitated the acquisition of the parenting skills being taught on the programme. It is argued that while prison based parenting programmes can improve parenting skills and father-child relationships, their potential long-term effectiveness may be limited by wider prison policies, procedures and practices surrounding prison visitation, telephone access and the progression of fathers following the completion of such programmes. Recommendations and suggestions for future practice are offered.